Method for preparing aerogel by using crosslinking-agent-free Pickering emulsion template and application of aerogel

Through the Pickering emulsion template method without crosslinking agent, the mixture and heating induction of TEMPO oxidized nanocellulose and lemon essential oil are formed to form an oil gel with thermal stability and high gel strength, which solves the gel in the prior art The problem of poor agent effect is suitable for applications in the food industry.

CN119144042APending Publication Date: 2024-12-17ZHEJIANG OCEAN UNIV +2
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411248547.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Gel agents are required in the preparation process of existing oil gels. A single gel agent has poor effect and is unstable, making it difficult to widely use in the food industry.

Method used

Using the Pickering emulsion template method without crosslinking agent, the mixture and heating of TEMPO oxidized nanocellulose and lemon essential oil form hydrogen bond entanglement and covalent crosslinking, spontaneously forming aerosol with excellent thermal stability and mechanical properties. glue.

Benefits of technology

It can achieve the formation of oil gels with high gel strength, thermal stability and large specific surface area without adding gel agent, which solves the problems of gel agent dependence and structural properties, and meets the application needs of the food industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005031593380000081
    Figure BDA0005031593380000081
  • Figure HDA0005031593390000011
    Figure HDA0005031593390000011
  • Figure HDA0005031593390000012
    Figure HDA0005031593390000012
Patent Text Reader

Abstract

The invention relates to the technical field of fine chemicals, in particular to crosslinking-agent-free Pickering emulsion oil gel and a preparation method and application thereof.The preparation method comprises the following steps that S1, cellulose is subjected to TEMPO oxidation treatment and then subjected to high-pressure homogenization, and TEMPO oxidized nano cellulose is obtained; s2, mixing the TEMPO oxidized nanocellulose and lemon essential oil in proportion, and homogenizing to obtain Pickering emulsion; s3, carrying out heat preservation on the Pickering emulsion at the temperature of 70-90 DEG C for 6-12 hours to obtain Pickering emulsion gel, freezing the Pickering emulsion gel at the temperature of-80 + / -5 DEG C for 30-40 minutes until the Pickering emulsion gel is completely frozen, and carrying out freeze drying for 24-48 hours to obtain Pickering emulsion oil gel; and S4, soaking the Pickering emulsion oil gel in acetone for 6-12 hours, taking out the Pickering emulsion oil gel, and freeze-drying the Pickering emulsion oil gel for 24-48 hours to obtain the Pickering emulsion aerogel. The Pickering emulsion aerogel has better thermal stability, larger specific surface area, cumulative pore volume and average pore size, and is prepared without using a cross-linking agent for cross-linking.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fine chemicals, and in particular to a method for preparing aerogel using a cross-linking agent-free Pickering emulsion template and application thereof. Background Art

[0002] With the deepening understanding of the negative effects of saturated fats and trans fatty acids on human health, oleogels are considered to be effective substitutes. In the earliest studies of oleogels, oleogels (gelling agents) were usually added to oils and fats to induce the formation of oleogels by promoting the capture of network structures and restricting the free flow of oils and fats. The physicochemical properties and multifunctional characteristics of oleogels mostly depend on gelling agents and structural mechanisms, and the gelation mechanism of liquid oils is mainly dominated by non-covalent interactions between different molecules, and the type and strength of these interactions are greatly affected by the structure and properties of gelling factors. At present, even though the application of many gelling agents in food has been widely studied, it is still challenging to find economical, low-concentration, effective, and tolerant to processing conditions food-grade gelling agents.

[0003] The gelling agents for preparing oil gels mainly include low molecular weight gelling agents (such as plant sterols, waxes, monoglycerides, diglycerides, fatty alcohols, cinnamic acid and ceramides, etc. and their complexes) and high molecular weight gelling agents (polysaccharides and proteins, etc.). However, most gelling agents are not allowed to be used in food, which limits the application and development of oil gels in the food industry. Gelling agents may also cause changes in product quality. For example, the properties of wax are unstable after crystallization and are easily affected by external factors, which may affect the storage and shelf life of food. In order to solve the problems caused by single gelling agents, the exploration of the synergistic interaction between the components of food-grade composite gelling agents is also a major topic of oil gel. However, the gels produced by most synergistic combinations are weak and cannot provide the required functions in actual food systems.

[0004] In recent years, Pickering emulsion systems have been found to have potential applications in fat replacement and improving the quality of gel products. Nanocellulose has good biodegradability, biocompatibility and thermal stability. Edible vegetable oil gels prepared from nanocellulose by emulsion template method have attracted widespread attention due to their potential to replace saturated fat or trans fat in the food industry. However, the type and properties of nanocellulose, including fiber size, flexibility, surface acetylation and carboxyl substitution degree, will affect the emulsification or gel properties of nanocellulose. Summary of the invention

[0005] The purpose of the present invention is to solve the problem described in the above background technology that a gelling agent is needed in the current oil gel preparation process, and the gelling effect obtained by a single gelling agent is poor. A method and application of preparing aerogel by a cross-linking agent-free Pickering emulsion template are proposed. The preparation method can spontaneously form a gel without adding a gelling agent, and the formed gel has excellent thermal stability, gel strength and mechanical properties, and has a larger specific surface area.

[0006] The technical solution adopted by the present invention to solve the technical problem is: a method for preparing aerogel using a cross-linking agent-free Pickering emulsion template, the method comprising the following steps:

[0007] S1. Preparation of TEMPO-oxidized nanocellulose

[0008] The cellulose was TEMPO-oxidized and then homogenized under high pressure to obtain TEMPO-oxidized nanocellulose;

[0009] S2. Preparation of Pickering emulsion

[0010] The TEMPO oxidized nanocellulose is diluted with water and mixed with lemon essential oil in a certain proportion, and homogenized to obtain a Pickering emulsion;

[0011] S3. Preparation of Pickering emulsion oil gel

[0012] The Pickering emulsion is kept at a temperature of 70-90° C. for 6-12 hours to obtain a Pickering emulsion gel, the Pickering emulsion gel is frozen at a temperature of -80±5° C. for 30-40 minutes until it is completely frozen, and then freeze-dried for 24-48 hours to obtain a Pickering emulsion oil gel;

[0013] S4. Preparation of Pickering emulsion aerogel

[0014] The Pickering emulsion oil gel is soaked in acetone for 6-12 hours, taken out, and freeze-dried for 24-48 hours to obtain the Pickering emulsion aerogel.

[0015] In the above technical scheme, a heating-induced method is adopted to promote the hydrogen bond entanglement between nanocellulose particles. The oil droplets are trapped in the oil gel, which is beneficial to the covalent cross-linking between the oil phase and the nanocellulose, thereby generating an oil gel in which a physical gel and a chemical gel coexist. Hydrogen bonding is the main driving force for the formation of the network. Compared with the aerogel prepared by adding a gelling agent in the prior art, the Pickering emulsion aerogel prepared by the present invention has better gel strength, thermal stability, larger specific surface area, cumulative pore volume and average pore size.

[0016] The TEMPO is a 2,2,6,6-tetramethylpiperidinyloxy free radical.

[0017] Preferably, step S1 is specifically as follows:

[0018] The cellulose is dispersed in water, NaBr, TEMPO and NaClO are added and mixed evenly, and then NaOH is added to adjust the pH to 9-11 to obtain a mixed solution, and the reaction is continued by stirring for 4-6 hours. The mixed solution is mixed with anhydrous ethanol at a mass ratio of 1:1 to terminate the reaction, and the TEMPO oxidized cellulose is obtained by suction filtration. The TEMPO oxidized cellulose is washed and centrifuged until the conductivity of the filtrate is less than 20 μS·cm -1 The filtered residue is pulped and homogenized multiple times to obtain TEMPO-oxidized nanocellulose.

[0019] The mass ratio of cellulose, NaBr, TEMPO and NaClO in the mixed solution is 20:2:0.32:49-147.

[0020] The above TEMPO oxidation reaction time is 4-6 hours, but the oxidation time is not limited thereto and can be increased with the increase in the amount of raw materials such as cellulose, NaCIO, and TEMPO.

[0021] Preferably, the mass ratio of cellulose, NaBr, TEMPO and NaClO in the mixed solution is 20:2:0.32:98.

[0022] Preferably, the specific conditions of the multiple homogenizations are: 700 bar homogenization for 2 cycles, each cycle for 20-30 min; 1000 bar homogenization for 3 cycles, each cycle for 20-30 min; 1400 bar homogenization for 5 cycles, each cycle for 20-30 min.

[0023] Homogenization is a common operation term in this field. From feeding to discharging under a certain pressure is counted as one time, from feeding to discharging under a certain pressure is repeated twice as two times, and so on. The use of gradually progressive homogenization pressure and cycle can better achieve the homogenization effect of the product, thereby improving the quality and stability of the product.

[0024] Preferably, the cellulose is selected from one or more of softwood needle cellulose, broadleaf eucalyptus cellulose and bamboo cellulose, and more preferably softwood needle cellulose.

[0025] Preferably, in step S2, the mass ratio of the lemon essential oil to water is 1:3-7, and the mass fraction of TEMPO-oxidized nanocellulose in the Pickering emulsion is 0.8-1.0%. Further preferably, the mass ratio of the lemon essential oil to water is 1:5, and the mass fraction of TEMPO-oxidized nanocellulose in the Pickering emulsion is 0.8%.

[0026] Preferably, in step S2, during the homogenization process, the temperature of the mixed solution of TEMPO-oxidized nanocellulose and lemon essential oil is controlled to be 5-15°C, the homogenization time is 8-15min, and the homogenization rate is 10000-20000rpm / min. More preferably, the temperature of the mixed solution of TEMPO-oxidized nanocellulose, water and lemon essential oil is controlled to be 10°C, the homogenization time is 9min, and the homogenization rate is 15000rpm / min.

[0027] Preferably, step S3 is specifically as follows: keeping the Pickering emulsion at 80°C for 12 hours to obtain a Pickering emulsion gel, freezing the Pickering emulsion gel at -80°C for 30 minutes until it is completely frozen, and then freeze-drying for 48 hours to obtain a Pickering emulsion oil gel.

[0028] Preferably, step S4 is specifically as follows: soaking the Pickering emulsion oil gel in acetone for 6 hours or 12 hours, taking it out, and freeze-drying it for 48 hours to obtain the Pickering emulsion aerogel.

[0029] In the above technical solution, if the heating temperature of the Pickering emulsion is too high, the appearance of the emulsion gel will be affected, and the emulsion gel will shrink and be filled with bubbles. If the heating temperature is too low, the emulsion gel cannot be formed.

[0030] A Pickering emulsion aerogel prepared by the method as described above.

[0031] An application of the Pickering emulsion aerogel in food as described above can be used to deliver lipophilic nutrients and provide a new design for functional health foods of solid fats.

[0032] The beneficial effects of the present invention are:

[0033] 1. In the present invention, a low internal phase Pickering emulsion with lemon essential oil as the oil phase is used, hydrogen bonds and entanglements between cellulose particles are formed under heating in a constant temperature water bath, oil droplets are trapped in the oil gel, and covalent cross-linking polymerization between lemon essential oil and nanocellulose is performed to form a gel in which physical gel and chemical gel coexist. In this process, gel can be formed spontaneously without adding a gelling agent.

[0034] 2. The Pickering emulsion oil gel prepared by the present invention can further remove the free oil phase remaining in the Pickering emulsion oil gel under acetone immersion, effectively improve the thermal stability of the aerogel (the lowest decomposition temperature is 204°C), and has a larger specific surface area (12.3385m 2 / g), cumulative pore volume (0.028cm 3 / g) and average pore size (8.88nm), the particles swell and the molecular structure stretches, resulting in larger voids, which solves the current situation that oil gels rely on gelling agents and are affected by the structural properties of gelling factors.

[0035] 3. The Pickering emulsion aerogel prepared by the present invention is based on nanocellulose, has no other cross-linking agents, is non-toxic and harmless, does not produce toxic gases, and can be recycled and degraded, which is in line with the concept of green development.

[0036] 4. The production steps of the present invention are simple, the cost of the raw materials used is low, and it is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is the appearance of the Pickering emulsions prepared in Example 1 and Comparative Examples 1 and 2 before heating;

[0038] Figure 2 This is the appearance of the Pickering emulsion prepared in Example 1 and Comparative Examples 1 and 2 after heating for 3 hours;

[0039] Figure 3 The constant temperature heating storage modulus diagram of the Pickering emulsion prepared in Example 1 and Comparative Examples 1 and 2;

[0040] Figure 4 The constant temperature heating loss modulus diagram of the Pickering emulsion prepared in Example 1 and Comparative Examples 1 and 2;

[0041] Figure 5 This is a graph of energy loss during constant temperature heating of the Pickering emulsions prepared in Example 1 and Comparative Examples 1 and 2;

[0042] Figure 6 This is the appearance of the Pickering emulsion gel prepared in Example 2 and Example 3;

[0043] Figure 7 This is a gel strength analysis diagram of the Pickering emulsion gel prepared in Example 2 and Example 3;

[0044] Figure 8 This is a moisture analysis chart of the Pickering emulsion gel prepared in Example 2 and Example 3;

[0045] Fig. 9 The infrared spectrum (FTIR) analysis diagram of lemon essential oil, TEMPO-oxidized nanocellulose, and the Pickering emulsion gas / oil gel prepared in Examples 2 and 3 and Comparative Examples 3 and 4;

[0046] Fig.10 X-ray diffraction (XRD) patterns of the Pickering emulsion gas / oil gels prepared by TEMPO-oxidized nanocellulose, Examples 2 and 3, and Comparative Examples 3 and 4;

[0047] Fig.11This is a thermal stability (TG) analysis chart of the Pickering emulsion gas / oil gel prepared by TEMPO-oxidized nanocellulose, Examples 2, 3, and Comparative Examples 3, 4;

[0048] Fig.12 This is a thermal stability (DTG) analysis diagram of the Pickering emulsion gas / oil gel prepared by TEMPO-oxidized nanocellulose, Examples 2, 3, and Comparative Examples 3, 4;

[0049] Fig.13 The microscopic morphology (SEM) analysis diagram of the Pickering emulsion oil gel prepared in Examples 2 and 3 and Comparative Examples 3 and 4, where (a) is NAE6 and (b) is NAE 12 , (c) is Ae6, (d) is Ae 12 . DETAILED DESCRIPTION

[0050] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0051] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0052] The present invention is now further described in conjunction with specific examples. The following examples are only for explaining the present invention, but do not constitute a limitation of the present invention. The test samples and test processes used in the following examples include the following (if the specific experimental conditions are not indicated in the examples, they are usually in accordance with conventional conditions or the conditions recommended by the reagent company; the reagents, consumables, etc. used in the following examples, if not otherwise specified, can all be obtained from commercial channels).

[0053] In this embodiment, the cork needle cellulose was purchased from Jining Nantian Agricultural Science and Chemical Co., Ltd., and the other reagents were purchased from Sinopharm Chemical Reagent Co., Ltd.

[0054] Example 1

[0055] A method for preparing a crosslinking agent-free Pickering emulsion, the preparation method specifically comprising:

[0056] S1. Place 20 g of softwood needle cellulose and 2 L of ultrapure water on a magnetic stirrer and stir. Add 2 g of NaBr, 0.32 g of TEMPO, and 40 mL of NaClO and mix well. Continue stirring for 4 h, and then add 0.5 M NaOH to adjust the pH of the solution to about 10.

[0057] S2. The mixed solution after the reaction in S1 was added to anhydrous ethanol at a mass ratio of 1:1 to terminate the reaction, and TEMPO oxidized cellulose was obtained by suction filtration. The obtained TEMPO oxidized cellulose was centrifuged and filtered until the conductivity of the filtrate was less than 20 μS·cm -1 The filter residue was beaten with a beater, and after beating, it was placed in a homogenizer for multiple homogenization to obtain TEMPO oxidized nanocellulose. The specific homogenization parameters were: two cycles at 700 bar, three cycles at 1000 bar, and five cycles at 1400 bar.

[0058] S3. The TEMPO oxidized nanocellulose prepared in S2 and lemon essential oil were mixed in proportion, and emulsified at a rotation speed of 15000 rpm for 9 minutes to obtain a Pickering emulsion (denoted as A), wherein the mass ratio of lemon essential oil to water was 1:5, and the mass fraction of TEMPO oxidized nanocellulose in the Pickering emulsion was 0.8%.

[0059] S4. Heat the Pickering emulsion prepared in S3 in a water bath at 80°C for 3 h.

[0060] Comparative Example 1

[0061] A method for preparing a cross-linking agent-free Pickering emulsion, the preparation method is the same as Example 1, except that lemon essential oil is replaced by peanut oil to prepare the Pickering emulsion (denoted as B).

[0062] Comparative Example 2

[0063] A method for preparing a cross-linking agent-free Pickering emulsion, the preparation method is the same as Example 1, except that lemon essential oil is replaced by dodecane to prepare the Pickering emulsion (denoted as C).

[0064] The state of the Pickering emulsions prepared in Example 1 and Comparative Examples 1 and 2 before and after heating is as follows Figure 1 and Figure 2 As shown, it can be seen that only the emulsion with lemon essential oil as the oil phase forms a stable and elastic hydrogel, while the emulsions with dodecane or peanut oil as the oil phase cannot form a relatively stable emulsion gel. This may be caused by the covalent cross-linking polymerization formed between lemon essential oil and TEMPO-oxidized nanocellulose.

[0065] The Pickering emulsions prepared in Example 1 and Comparative Examples 1 and 2 were subjected to constant temperature heating rheological property analysis and the results are as follows: Figure 3-5 As shown, it can be seen that by comparing the gel G' values, it is found that lemon essential oil>dodecane>peanut oil, indicating that the emulsion with lemon essential oil as the oil phase is superior to the emulsion with peanut oil or dodecane as the oil phase in terms of gelation speed and gelation strength.

[0066] Example 2

[0067] A method for preparing a crosslinking agent-free Pickering emulsion aerogel, the preparation method specifically comprising:

[0068] S1. Place 20 g of softwood needle cellulose and 2 L of ultrapure water on a magnetic stirrer and stir. Add 2 g of NaBr, 0.32 g of TEMPO, and 40 mL of NaClO and mix well. Continue stirring for 4 h, and then add 0.5 M NaOH to adjust the pH of the solution to about 10.

[0069] S2. The mixed solution after the reaction in S1 was added to anhydrous ethanol at a mass ratio of 1:1 to terminate the reaction, and TEMPO oxidized cellulose was obtained by suction filtration. The obtained TEMPO oxidized cellulose was centrifuged and filtered until the conductivity of the filtrate was less than 20 μS·cm -1 The filter residue was beaten with a beater, and after beating, it was placed in a homogenizer for multiple homogenization to obtain TEMPO oxidized nanocellulose. The specific homogenization parameters were: two cycles at 700 bar, three cycles at 1000 bar, and five cycles at 1400 bar.

[0070] S3. The TEMPO oxidized nanocellulose prepared in S2 and lemon essential oil were mixed in proportion, and emulsified at a rotation speed of 15000 rpm for 9 minutes to obtain a Pickering emulsion, wherein the mass ratio of lemon essential oil to water was 1:5, and the mass fraction of TEMPO oxidized nanocellulose in the Pickering emulsion was 0.8%.

[0071] S4. Heat the Pickering emulsion prepared in S3 in a water bath at 80°C for 6 hours, freeze it at -80°C for 30 minutes to completely freeze it, and freeze-dry it in a freeze dryer for 48 hours to obtain the Pickering emulsion oil gel.

[0072] S5. The Pickering emulsion oil gel prepared in S4 was soaked in acetone for 6 hours to completely remove the free oil phase remaining in the oil gel. The oil gel after soaking in acetone was placed in a vacuum freeze dryer again for freeze drying for 48 hours to obtain the Pickering emulsion aerogel (denoted as Ae6).

[0073] Comparative Example 3

[0074] A method for preparing a cross-linking agent-free Pickering emulsion oil gel, the preparation method is the same as Example 2, except that, in step S5, the Pickering emulsion oil gel prepared in step S4 is not subjected to acetone immersion (6h) and a second vacuum freeze-drying for 48h to obtain the Pickering emulsion oil gel (denoted as NAe6).

[0075] Example 3

[0076] A method for preparing a crosslinking agent-free Pickering emulsion aerogel, the preparation method specifically comprising:

[0077] S1. Place 20 g of softwood needle cellulose and 2 L of ultrapure water on a magnetic stirrer and stir. Add 2 g of NaBr, 0.32 g of TEMPO, and 40 mL of NaClO and mix well. Continue stirring for 4 h, and then add 0.5 M NaOH to adjust the pH of the solution to about 10.

[0078] S2. The mixed solution after the reaction in S1 was added to anhydrous ethanol at a mass ratio of 1:1 to terminate the reaction, and TEMPO oxidized cellulose was obtained by suction filtration. The obtained TEMPO oxidized cellulose was centrifuged and filtered until the conductivity of the filtrate was less than 20 μS·cm -1 The filter residue was beaten with a beater, and after beating, it was placed in a homogenizer for multiple homogenization to obtain TEMPO oxidized nanocellulose. The specific homogenization parameters were: two cycles at 700 bar, three cycles at 1000 bar, and five cycles at 1400 bar.

[0079] S3. The TEMPO oxidized nanocellulose prepared in S2 and lemon essential oil were mixed in proportion, and emulsified at a rotation speed of 15000 rpm for 9 minutes to obtain a Pickering emulsion, wherein the mass ratio of lemon essential oil to water was 1:5, and the mass fraction of TEMPO oxidized nanocellulose in the Pickering emulsion was 0.8%.

[0080] S4. Heat the Pickering emulsion prepared in S3 in a water bath at 80°C for 12 h, freeze it at -80°C for 30 min to completely freeze it, and freeze-dry it in a freeze dryer for 48 h to obtain the Pickering emulsion oil gel.

[0081] S5, the Pickering emulsion oil gel prepared in S4 was placed in acetone for 12 hours to completely remove the free oil phase remaining in the oil gel, and the oil gel after soaking in acetone was placed in a vacuum freeze dryer for 48 hours to obtain the Pickering emulsion aerogel (denoted as Ae 12 ).

[0082] Comparative Example 4

[0083] A method for preparing a crosslinking agent-free Pickering emulsion oil gel, the preparation method is the same as Example 3, except that the Pickering emulsion oil gel prepared in step S5 is not subjected to acetone soaking (12h) and vacuum freeze drying for a second time for 48h to obtain the Pickering emulsion oil gel (denoted as NAe 12 ).

[0084] The porosity and mechanical properties of the Pickering emulsion gas / oil gels prepared in Examples 2 and 3 and Comparative Examples 3 and 4 were tested. The test results are shown in Table 1.

[0085] The porosity detection method is: BET analysis is performed using the Micromeritics ASAP 2020 fully automatic specific surface area and porosity analyzer (Micromeritics, USA) and its software.

[0086] The mechanical properties testing method is: using UTM4103 microcomputer-controlled electronic universal testing machine (China) and its software to perform low-load pressure rebound analysis. That is, using this instrument to perform compression testing, loading the material at a certain loading rate to a specified stress or strain, and then stopping loading, and unloading at a specified unloading rate. When the stress is unloaded to zero, the remaining value of the strain is the part of the material that has not rebounded after this compression cycle.

[0087] Table 1 Porosity and mechanical properties of Pickering emulsion gas / oil gels prepared in Examples 2, 3 and Comparative Examples 3, 4

[0088]

[0089]

[0090] By comparing Example 2 and Comparative Example 3, and Example 3 and Comparative Example 4, it can be seen that the Pickering emulsion aerogel subjected to acetone immersion treatment has a larger specific surface area, cumulative pore volume and average pore size than the Pickering emulsion oil gel that has not been soaked in acetone, and has a lower 98% compressive strength and 98% compression modulus, indicating that the swollen fiber structure in the Pickering emulsion aerogel is conducive to the penetration of other substances and the preparation of ultra-light materials. Soaking in acetone to further remove part of the oil phase remaining in the Pickering emulsion oil gel will make the emulsion oil gel more rigid and more brittle. This may be because the oil phase of the free lemon essential oil will have a certain wetting effect on the cellulose three-dimensional network of the emulsion oil gel.

[0091] From the comparison between Comparative Example 3 and Comparative Example 4, it can be seen that the Pickering emulsion oil gel prepared in Comparative Example 3 has higher 98% compression strength and 98% compression modulus, which indicates that the extension of heating time makes the emulsion oil gel more elastic and has a better gel effect.

[0092] like Figure 6 As shown, it is the appearance of the Pickering emulsion aerogel prepared in Example 2 and Example 3. Both have been formed, with no obvious difference in appearance, a uniform and smooth surface, and the morphology of the emulsion aerogel has not changed due to gravity, and both can maintain their original shape after demolding.

[0093] The gel strength test of the Pickering emulsion gel prepared in Example 2 and Example 3 was performed, and the test results are as follows: Figure 7 As shown, it can be seen that Ae 12 The gel strength of Ae6 is 12% higher than that of Ae6, indicating that the increase in gel strength may be due to the longer heating time during the heat-induced gelation process, which causes more water to evaporate, resulting in the emulsion gel forming a denser cellulose three-dimensional network structure, and a certain degree of covalent cross-linking between TEMPO-oxidized nanocellulose and lemon essential oil.

[0094] like Figure 8 As shown, Ae6 and Ae 12 The bound water (T 2b ) accounted for 72.43% and 73.97% respectively, Ae 12 T 2b The proportion of T is greater than Ae6 2b The proportion of free water in the emulsion gel system shows that with the extension of heating time, the free water content in the emulsion gel system gradually decreases, and its quality characteristics are closer to gel properties. 12 The relaxation time is less than Ae 62 The relaxation time of 2.5 Å indicates that under the induction of heating, the degree of cross-linking between nanocellulose and emulsion droplets increases, forming a denser three-dimensional gel network, and thus the flowable water content decreases.

[0095] like Fig. 9 As shown, at 2922cm -1 The peaks observed at 1443 cm-1 are probably related to the CH stretching of CH3 and CH2, which are derived from TEMPO-oxidized nanocellulose and lemon essential oil with a charge density of 662 μmol / g. -1 and 1376cm -1 The peak at 880 cm-1 confirms the presence of CH bending of CH3 and CH2 groups, which is related to lemon essential oil and polysaccharides. -1 and 1673cm -1 The peaks at 1673 cm-1 are related to the bending vibration of =CH of R2C=CH2 and the stretching vibration of CH of C=C. -1 The intensity at NAe6 and NAe7 is lower than that of lemon essential oil, which may be due to the covalent cross-linking polymerization between TEMPO-oxidized nanocellulose and lemon essential oil.12 , Ae6 and Ae 12 There was no significant difference in the FTIR spectra of the samples. For the polymer oil gel, hydrogen bonds attached to the single -OH groups play an important role in generating network formation. Polymer gels are formed by self-assembly mechanisms of hydrogen bonds or van der Waals forces or covalent bonds between polymer chains, which produce physical gels or chemical gels, respectively. The results show that the oil gel based on the emulsion with lemon essential oil as the oil phase is an emulsion oil gel with both chemical covalent cross-linked polymer gel and physical gel, and hydrogen bonds are the main driving force for network formation.

[0096] like Fig.10 As shown, the curve shows the typical cellulose structure, TEMPO-oxidized nanocellulose, NAE6, NAE 12 , Ae6 and Ae 12 All exhibit a typical Iβ crystal structure with distinct crystallization peaks at 16°, 22.5°, and 34.5°, corresponding to reflection planes (110), (200), and (004), respectively, indicating that the typical crystal structure remains unchanged after heating gel treatment.

[0097] like Fig.11 , 12 As shown, TEMPO-oxidized nanocellulose, NAe6, and NAe 12 , Ae6 and Ae 12 The residual masses at 800℃ are 13.7%, 7.28%, 6.07%, 16.05% and 15.24% respectively. 12 The decrease in the residual mass of TEMPO-oxidized nanocellulose can be attributed to the partial destruction of the thermally stable crystalline structure or the degradation of TEMPO-oxidized nanocellulose promoted by the addition of lemon essential oil. 12 The lower residual mass than NAe6 may be due to the destruction of the cellulose crystal structure caused by the prolonged heating time. 12 The thermal properties of the oil gel were improved, which may be attributed to the fact that the acetone immersion further removed part of the oil phase remaining in the oil gel, and the oil phase bound to the nanocellulose improved the thermal stability of the gel.

[0098] like Fig.13 As shown, Ae6 and Ae 12 There are many protruding particles scattered on the surface of Ae6, which may be lemon essential oil covalently cross-linked with nanocellulose. 12 Compared with NAe 12 The fiber network is more expanded, which should be due to the gel being soaked in acetone, which causes the particles to expand and the molecular structure to stretch, thus creating larger voids.

[0099] In summary, Ae12 It can further remove the free oil phase remaining in the aerogel, effectively improve the thermal stability of the aerogel (the lowest decomposition temperature is 204°C), and have a larger specific surface area (12.3385m 2 / g), cumulative pore volume (0.028cm 3 / g) and average pore size (8.88nm), the particles expanded and the molecular structure stretched, resulting in larger voids.

[0100] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0101] The above is a detailed introduction to the method and application of preparing aerogels by a cross-linking agent-free Pickering emulsion template provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing aerogel using a crosslinker-free Pickering emulsion template, characterized in that: The method comprises the following steps: S1. Preparation of TEMPO-oxidized nanocellulose Cellulose was treated with TEMPO oxidation and then homogenized under high pressure to obtain TEMPO-oxidized nanocellulose; S2. Preparation of Pickering emulsion The TEMPO oxidized nanocellulose is diluted with water and mixed with lemon essential oil in a certain proportion, and homogenized to obtain a Pickering emulsion; S3. Preparation of Pickering emulsion oil gel The Pickering emulsion is kept at a temperature of 70-90° C. for 6-12 hours to obtain a Pickering emulsion gel, the Pickering emulsion gel is frozen at a temperature of -80±5° C. for 30-40 minutes until it is completely frozen, and then freeze-dried for 24-48 hours to obtain a Pickering emulsion oil gel; S4. Preparation of Pickering emulsion aerogel The Pickering emulsion oil gel is soaked in acetone for 6-12 hours, taken out, and freeze-dried for 24-48 hours to obtain the Pickering emulsion aerogel.

2. The method according to claim 1, characterized in that: Step S1 is specifically as follows: The cellulose is dispersed in water, NaBr, TEMPO and NaClO are added and mixed evenly, and then NaOH is added to adjust the pH to 9-11 to obtain a mixed solution, and the reaction is continued by stirring for 4-6 hours. The mixed solution is mixed with anhydrous ethanol at a mass ratio of 1:1 to terminate the reaction, and the TEMPO oxidized cellulose is obtained by suction filtration. The TEMPO oxidized cellulose is washed and centrifuged until the conductivity of the filtrate is less than 20 μS·cm -1 The filtered residue is pulped and homogenized multiple times to obtain TEMPO-oxidized nanocellulose, and the mass ratio of cellulose, NaBr, TEMPO and NaClO in the mixed solution is 20:2:0.32:49-147.

3. The method according to claim 2, characterized in that: The mass ratio of cellulose, NaBr, TEMPO and NaClO in the mixed solution is 20:2:0.32:

98.

4. The method according to claim 2, characterized in that: The specific conditions of the multiple homogenizations are: 700 bar homogenization for 2 cycles, each cycle for 20-30 minutes; 1000 bar homogenization for 3 cycles, each cycle for 20-30 minutes; 1400 bar homogenization for 5 cycles, each cycle for 20-30 minutes.

5. The method according to claim 1, characterized in that: The cellulose is selected from one or more of softwood needle cellulose, broadleaf eucalyptus cellulose and bamboo cellulose.

6. The method according to claim 1, characterized in that: In step S2, the mass ratio of the lemon essential oil to water is 1:3-7, and the mass fraction of TEMPO-oxidized nanocellulose in the Pickering emulsion is 0.8-1.0%.

7. The method according to claim 1, characterized in that: Step S2, during the homogenization process, the temperature of the mixed solution of TEMPO-oxidized nanocellulose and lemon essential oil is controlled to be 5-15°C, the homogenization time is 8-15min, and the homogenization rate is 15000rpm / min.

8. The method according to claim 1, characterized in that: Step S3 is specifically as follows: keeping the Pickering emulsion at 80°C for 12 hours to obtain a Pickering emulsion gel, freezing the Pickering emulsion gel at -80°C for 30 minutes until it is completely frozen, and then freeze-drying it for 48 hours to obtain a Pickering emulsion oil gel.

9. The method according to claim 1, characterized in that: Step S4 specifically comprises: soaking the Pickering emulsion oil gel in acetone for 6 hours or 12 hours, taking it out, and freeze-drying it for 48 hours to obtain the Pickering emulsion aerogel.

10. Use of the Pickering emulsion aerogel prepared by the method according to any one of claims 1 to 9 in food.

Citation Information

Cited By

  • Method for enriching new pollutants in water through cooperation of microorganisms and free-state manganese

    CN119118432A

  • Composite hydrogel and preparation method thereof

    CN120484284A

  • High-efficiency heat-insulation composite aerogel for preserving chilled fresh meat as well as preparation method and application of high-efficiency heat-insulation composite aerogel

    CN122188221A

  • High-efficiency heat insulation composite aerogel for fresh chilled meat preservation and preparation method and application thereof

    CN122188221B